Practicability and user-friendliness of height measurements by proof of concept APP using Augmented Reality, in 22 healthy children - Antonia Rösler; Nikolaos Gasparatos; Michael Hermanussen; Christiane Scheffler (Human Biology and Public Health, 2022)
Background: Child growth is a dynamic process. When measured at short intervals, children’s growth shows characteristic patterns that can be of great importance for clinical purposes.